VIDEOLARYNGOSCOPE VERSUS TRADITIONAL LARYNGOSCOPY FOR COMPARISON OF EASE OF INTUBATION AND HEMODYNAMIC CHANGES – A PROSPECTIVE RANDOMIZED STUDY - Singh, Tanya; Rekhi, Balwinder Kaur; Kumar, Parmod; Kaur, Mandeep (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The objective of the study is to compare ease of intubation and hemodynamic changes with video laryngoscope (VL) (C-MAC) versus traditional laryngoscopy and to assess any complication such as arrhythmias, local injuries, bleeding, laryngospasm, regurgitation during intubation, and sore throat post-intubation. Methods: This prospective randomized study was conducted on 200 patients of Mallampati (MP) Grades 1 and 2, ASA-PS I and II, randomly allocated to Group M (Macintosh) and Group V (C-MAC) (n=100 each). Hemodynamic changes (heart rate, systolic blood pressure, diastolic blood pressure, mean arterial pressure [MAP], SpO2, and EtCO2) were recorded at baseline, during pre-oxygenation, during laryngoscopy, and during intubation, at 1 min, 3 min, 5 min, and then, at 10 min after endotracheal intubation. Ease of intubation and any complications were also recorded. Results: Laryngeal view was significantly better in Group V. The mean heart rate during laryngoscopy and intubation (L&I) and after endotracheal intubation at 3rd min (ETI3); mean systolic blood pressure during L&I and after ETI1, ETI3, and ETI5 min; mean diastolic blood pressure after ETI1 and ETI min; and mean MAP during L&I and after ETI1 min were found to be significantly higher in Group M as compared to Group V (p<0.05). The difference in mean SPO2 and ETCO2 between the two groups was not found to be significant at any time interval. No significant difference was observed with respect to complications. Conclusion: Group V (VL C-MAC) showed better ease of intubation, decreased hemodynamic response, and fewer complications as compared to Group M (Macintosh laryngoscope).